Under new management Australian organizations in transition - Dunphy, Dexter (McGraw-Hill, 1992)
There is an organizational and managerial revolution sweeping through Australia's organizations. This important book is about bold and successful strategies for the redirection and renewal of our organizations to meet the challenges of global economic reorganization and increasing competition.